Developing Conflict Resolution Skills Through Scouting Activities at Elementary Schools - Sa'odah Sa'odah; Bunyamin Maftuh; Elly Malihah; Sapriya Sapriya (AL-ISHLAH: Jurnal Pendidikan, 2023)
The ability to overcome and solve conflicts is a skill that everyone should have. This skill must be taught to students at every level of education in a systematic and structured manner. This study aimed to analyze the urgency of developing a scout activity-based conflict resolution model in elementary schools. This study used a descriptive qualitative approach. The data were collected through interviews conducted with teachers and students, as well as observations on scout activities in elementary schools and used a literature study to describe the application of the conflict resolution model based on several experts and supporting reference studies. The respondents were from 10 elementary schools in the Tangerang area that were selected by using a purposive random sampling technique with 10 Teachers and 30 students. The data were analyzed to determine the urgency of developing a scouting activity-based conflict resolution model in elementary schools. This study used a qualitative descriptive method and used a literature study. The results of the study showed that (1) Scouting activities have great potential to train conflict resolution skills, especially for students in elementary schools, (2) Scouting activities have not been optimized as a means of developing conflict resolution skills, (3) Developing conflict resolution skills also as a means in developing communication skills, self-confidence, adaptation, critical thinking, negotiation, and democracy. The results of this study are expected to provide alternative models of character education and increase students' capacities in overcoming and solving conflicts through scouting activities.